The dog that would never bite? The past and future of the Stability and Growth Pact - Martin Heipertz; Amy Verdun (Max Planck Institute for the Study of Societies, 2003)
This paper analyses the underlying reasons for the creation of the Stability and Growth Pact (SGP) and its subsequent development in recent years. The paper examines the economic and political factors behind it, including the role of economic ideas, experts, politicians, institutional arrangements in the Maastricht Treaty, domestic politics, and the exceptional position of Germany in the realm of monetary integration in the EU. It concludes that a set of commonly held beliefs together with a corresponding power-political constellation explain the creation of the SGP. – – Das Papier analysiert die grundlegenden Bedingungen für das Zustandekommen des Stabilitäts- und Wachstumspakts (SGP) und seiner Entwicklung in den Folgejahren. Es werden ökonomische und politische Faktoren untersucht, insbesondere die Rolle wirtschaftspolitischer Vorstellungen und den Einfluss von Experten, Politikern, institutioneller Regelungen im Maastricht Vertrag, innenpolitischer Vorgänge und die Sonderstellung Deutschlands im Bereich der Europäischen Währungsunion. Die gemeinschaftlichen wirtschaftspolitischen Vorstellungen werden als notwendige Bedingung für die Schaffung des Paktes aufgefasst, und ihr Zusammentreffen mit einer entsprechenden machtpolitischen Spielkonstellation wird als dessen hinreichende Erklärung verstanden.
Keywords: 300